R&D spending and patents: levers of national development - Fabio de Oliveira Paula; Jorge Ferreira da Silva (Innovation & Management Review, 2021)
Purpose - The level of R&D spending of a country tends to increase the national patent rate and, in consequence, can collaborate with its economic development. However, there are a few empirical studies investigating this phenomenon by comparing countries from all over the globe. The purpose of this paper is to disassemble the sources of R&D spending and identify the role of national patent applications as a mediator in the relationship between R&D spending and national development. Design/methodology/approach - Panel data on patent applications in 35 countries of all continents (except Africa) over 15 years (from 1999 to 2013) regarding four levels of national R&D intensity (i.e. by enterprises, governments, higher education institutions and private non-profit organisations), gross domestic product (GDP) per capita, gross national income (GNI) and human development index (HDI) were collected from the OCDE. Then, two-stage panel regressions were conducted to test the hypotheses. Findings - The empirical findings indicated that R&D spending from firms and higher education institutions (public and private) help to directly improve national patent applications, thus contributing to the national development (measured by GDP per capita, GNI per capita and HDI). Originality/value - The importance of this study was to show that the investments in R&D made by universities and firms are more effective in leading to patent applications, which contributes to promoting national development. With these findings, governments can focus their efforts on stimulating these types of investments if they want to foster the growth of national patent rates.
Keywords: 650; Innovation; National development; Patent applications; R&D spending